A Modern Look on Rhesus-Conflict Pregnancy - Nazhmutdinova D. K.; Akhtamova Maftuna (Researchparks Publishing, 2021)
The article reflects modern ideas on the management of pregnant women with Rh-negative blood affiliation, the pathogenetic basis of the development of sensitization during pregnancy and modern methods of preventing Rh-conflict. The standards for providing medical care to Rh-negative women with physiological pregnancy and Rh-sensitization are presented. The role of ultrasound diagnostic methods in determining the degree of fetal anemization is shown. An algorithm for the observation of pregnant women with Rh negative blood affiliation and indications for intrauterine intravascular blood transfusion to the fetus are presented.